PENGARUH PROBIOTIK FMPLUS TERHADAP RECAHAN KARKAS DAN LEMAK ABDOMINAL BROILER FASE FINISHER - Helda Syarif; Catootjie L Nalle (Politeknik Pertanian Negeri Kupang, 2020)
The aim of this research was to evaluate the effect of Probio FMplus on carcass component parts and abdominal fat of growing broilers. A total of 150 day-old broiler chicks (unsexed, Cobbs strain) were used in the present study. The chicks were randomly distributed to 25 pens (6 birds/pen). The experiment was design by using a complete randomized design consisting of five treatments and five replications. The treatments were a control diet without the addition of probio FMplus in drinking water (R0), control diets added with 0.5% Probio FMplus (R1), control diets added with 1.0% Probio FMplus (R3), and control diets added with 2.0% Probio FMplus (R4). The variables measured were carcass component parts and abdominal fat percentage. The result showed that the treatments did not have any significant effects (P >0.5) on all parameters measured. However, numerically it seemed that the breast meat and thigh percentages of group of birds fed diets added with Probio FMplus were higher than those of control diets without Probio FMplus. In conclusion, the addition of Probio FMplus (0 to 2%) did not give any beneficial effects of carcass component parts and abdominal fat percentages. Further research is needed to evaluate the higher level of Probio FMplus. escortnavi Keywords: Abdominal fat, Broiler, Carcass, Symbiotic.